2022
DOI: 10.1007/s10459-022-10113-x
|View full text |Cite|
|
Sign up to set email alerts
|

Massive open online course adoption amongst newly graduated health care providers

Abstract: Massive Open Online Courses (MOOCs) are flexible offerings that deliver content to a large audience in a virtual platform. MOOCs are increasingly accessed by health professionals to support their own professional development. Despite the agreed usefulness of MOOCs, the rates of adoption are still extremely low. This study sought to understand the personal and social factors associated with MOOC adoption. Participants were newly graduated occupational therapists who registered for a leadership skills developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The improvement in completion rates in this study (78% for initial learning and 56% for completing all assignments) compared with our initial pilot may be attributed to the in-person support and the escalating nudging strategy. These rates are comparable to longitudinal e-learning studies in high-income countries (44%–50%),60 61 and significantly higher than massive open online courses rates (7%–15%) 62 63. Beyond our revised implementation strategy, other factors such as increased peer support and a higher percentage of providers participating in PACE at each facility may have contributed to improved completion rates.…”
Section: Discussionmentioning
confidence: 55%
“…The improvement in completion rates in this study (78% for initial learning and 56% for completing all assignments) compared with our initial pilot may be attributed to the in-person support and the escalating nudging strategy. These rates are comparable to longitudinal e-learning studies in high-income countries (44%–50%),60 61 and significantly higher than massive open online courses rates (7%–15%) 62 63. Beyond our revised implementation strategy, other factors such as increased peer support and a higher percentage of providers participating in PACE at each facility may have contributed to improved completion rates.…”
Section: Discussionmentioning
confidence: 55%
“…In many settings, consumers fail to maintain consumption of products they own despite the benefits of continued consumption. For example, while many consumers join massive open online courses (Baturay, 2015), a large majority abandon these courses prematurely, forgoing the potential for long‐term benefits (Duncan et al, 2022; Voudoukis & Pagiatakis, 2022). In some cases, this failure can be described as an indication of learned helplessness (Seligman, 1972; e.g., Peng & Xu, 2020): Consumers try to use the sophisticated features of a product but give up before mastering the skill or achieving their goal.…”
Section: The Potential Of a Prediction‐oriented Middle Groundmentioning
confidence: 99%
“…MOOC has the view to offer free and accessible education to anyone, particularly to people from developing countries (Alhazzani, 2020). Using MOOC allow a learner to improve their knowledge without being on campus regularly, they can join MOOC and keep their employment or even seek employment while studying (Duncan, 2022). Albelbisi et al (2021) indicated that the adoption of MOOCs covering a national curriculum can be seen as a contribution in solving the educational challenges in countries with a lower level of formal education or countries that need a rapid educational enhancement.…”
Section: Adoption Of Moocmentioning
confidence: 99%
“…MOOC has received significant attention in the higher education literature (e.g., Duncan, 2022). Many studies suggested that MOOCs have the capability to increase the accessibility to high-quality education and decrease higher education costs (Al-Adwan, 2020).…”
Section: Introductionmentioning
confidence: 99%